PERAN ATHLETICS SPRINT ACADEMY DALAM PEMBINAAN SPRINTER NTB - Rio Zaili; Rusdiana Yusuf; Kokom Supriyatnak (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
ABSTRACT Sprint athlete development in regional areas requires a well-planned training system, support from competent coaches, and sustainable organizational management to produce high-achieving athletes. This study aimed to describe the role of the Athletics Sprint Academy (ASA) Club in developing sprinter athletes to improve sports achievement in West Nusa Tenggara Province in 2025. The study employed a descriptive qualitative approach using the Context, Input, Process, Product (CIPP) evaluation model. The research subjects consisted of club administrators, coaches, and outstanding athletes of ASA Club. Data were collected through observation, semi-structured interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The findings showed that ASA has a clear development orientation as a regional sprinter training center. In the input aspect, the club is supported by coaches holding World Athletics Level 1 and 2 licenses, although it still faces limitations in training facilities and funding. In the process aspect, athlete development is carried out through structured training programs based on individualization, overload, specificity, periodization, physical monitoring, and mental support. In the product aspect, ASA athletes achieved accomplishments at regional and national levels during 2022–2024. The findings indicate that a community-based sports club can serve as an effective sprint development model when supported by strong organizational management, scientific training programs, and a sustainable development environment. ABSTRAK Pembinaan atlet sprint di daerah memerlukan sistem latihan yang terencana, dukungan pelatih kompeten, serta pengelolaan organisasi yang berkelanjutan agar mampu menghasilkan atlet berprestasi. Penelitian ini bertujuan mendeskripsikan peran Klub Athletics Sprint Academy (ASA) dalam pembinaan atlet sprinter untuk meningkatkan prestasi olahraga di Provinsi Nusa Tenggara Barat tahun 2025. Penelitian menggunakan pendekatan kualitatif deskriptif dengan model evaluasi Context, Input, Process, Product (CIPP). Subjek penelitian terdiri atas pengurus, pelatih, dan atlet berprestasi Klub ASA. Pengumpulan data dilakukan melalui observasi, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis melalui tahapan reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa ASA memiliki arah pembinaan yang jelas sebagai wadah pengembangan sprinter daerah. Pada aspek input, klub didukung pelatih berlisensi World Athletics Level 1 dan 2, meskipun masih menghadapi keterbatasan fasilitas latihan dan pendanaan. Pada aspek process, pembinaan dilaksanakan melalui program latihan terstruktur berbasis individualisasi, overload, spesifikasi, periodisasi, pemantauan fisik, dan dukungan mental atlet. Pada aspek product, atlet ASA berhasil meraih prestasi pada tingkat daerah dan nasional selama 2022–2024. Temuan penelitian menunjukkan bahwa klub berbasis komunitas dapat menjadi model pembinaan sprint yang efektif apabila didukung manajemen organisasi, program latihan ilmiah, dan lingkungan pembinaan yang berkelanjutan.